Terahertz bandwidth optical nonlinearity of graphene metamaterial - Atmatzakis, Evangelos (2013)
We provide the first observation that hybridizing graphene with plasmonic metamaterial results in order of magnitude resonant enhancement of its nonlinear optical properties and enables THz-bandwidth optical switching at near-infrared wavelengths.